Genesis and evolution of Comedy in the Western theater - Hamou, Hurea; Shaker, Ziad (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The comedy of the Leading Categories aesthetic, which is Linked to the theatrical art since ancient times to the present day, and the tendency to comedy, but a sense of spontaneous imposed by the nature of the emotional human beings, because of their aesthetic creative effect, contribute to some extent influence the human psyche, according to its degree and function assigned, and push forward the life forward, to keep the brand Arhaffha to our senses, including the people of extremes and is flawed, according to him should be.